Estrategias de marketing digital en Marieta Peluquería del Cantón Babahoyo provincia de los Ríos en el periodo 2023. - Martínez Lara, Digna Amada (2024)
This case study is focused on analyzing the digital marketing strategies used in Marieta Peluquería in the Babahoyo canton, province of Los Rios, and period 2023. Its owner Marieta Coello is the one who manages it, however, she does not have the necessary knowledge about Digital Marketing, so which the biggest problem of the business is the attention of the marketing strategies that exist, this means that currently the sales of the services offered have been decreasing and has negatively impacted the success and recognition of the company. This project aims to “Analyze the effectiveness of digital marketing strategies at Marieta Peluquería, due to the impact caused by the marketing of services to attract business customers. As a research method, inductive and deductive methods were used, based on the analysis of concrete and specific events that occurred in the company. The techniques used in this research were an interview directed at the owner of Marieta Peluquería and a survey applied to the inhabitants of the company. Babahoyo City. This shows that the hair salon does not have the necessary marketing strategies to attract new clients and maintain existing ones, which means that the sale of its services is not well received.